Short‐term fasting promotes insulin expression in rat hypothalamus. (13th June 2017) - Dakic, Tamara B.; Jevdjovic, Tanja V.; Peric, Mina I.; Bjelobaba, Ivana M.; Markelic, Milica B.; Milutinovic, Bojana S.; Lakic, Iva V.; Jasnic, Nebojsa I.; Djordjevic, Jelena D.; Vujovic, Predrag Z.
Abstract: In the hypothalamus, insulin takes on many roles involved in energy homoeostasis. Therefore, the aim of this study was to examine hypothalamic insulin expression during the initial phase of the metabolic response to fasting. Hypothalamic insulin content was assessed by both radioimmunoassay and Western blot. The relative expression of insulin mRNA was examined by qPCR. Immunofluorescence and immunohistochemistry were used to determine the distribution of insulin immunopositivity in the hypothalamus. After 6‐h fasting, both glucose and insulin levels were decreased in serum but not in the cerebrospinal fluid. Our study showed for the first time that, while the concentration of circulating glucose and insulin decreased, both insulin mRNA expression and insulin content in the hypothalamic parenchyma were increased after short‐term fasting. Increased insulin immunopositivity was detected specifically in the neurons of the hypothalamic periventricular nucleus and in the ependymal cells of fasting animals. These novel findings point to the complexity of mechanisms regulating insulin expression in the CNS in general and in the hypothalamus in particular. Abstract : Short‐term fasting increased the expression of insulin mRNA and protein insulin content in the rat hypothalamus. Increased insulin immunopositivity was detected in NeuN‐positive cells of periventricular nucleus and in ependymal cells around the third ventricle.